The Thoughts of West Kalimantan Scholars in Islamic Law: Contribution and Relevance in Islamic Religious Education Materials - Ilmi, Syaiful; Akbar, Taufik (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The integration of local scholars (‘ūlama’) thoughts into Islamic Religious Education materials in schools has been little discussed in the academic realm. This article aims to reveal the thoughts of West Kalimantan scholars on Islamic law and its relevance to Islamic religious education materials in schools. This type of research uses a qualitative approach to library research and historical studies. The historical approach the author uses to trace the development of thought among West Kalimantan scholars, especially in the field of Islamic law. The findings of this study demonstrate that the thinking of West Kalimantan scholars in Islamic law is relevant to Islamic religious education materials at the high school level. The findings of this research are based on the thoughts of H. Ismail Mundu, as presented in his works, namely, Kitāb Jaduwal Nikah, which discusses marriage, and Kitāb Majmu’ al-Mirath fi hukm al-Faraid, which explores the science of inheritance law. This research has limitations because it only focuses on Ismail Mundu’s thoughts on Islamic Law. Further research can compare the thoughts of West Kalimantan scholars and their relevance in Islamic religious education materials.